Conflicts, crimes and regulations in cyberspace - e (Wiley, 2021)
The study of cyberspace is relatively new within the field of social sciences, yet interest in the subject is significant. Conflicts, Crimes and Regulations in Cyberspace contributes to the scientific debate being brought to the fore by addressing international and methodological issues, through the use of case studies. This book presents cyberspace as a socio-technical system on an international level. It focuses on state and non-state actors, as well as the study of strategic concepts and norms. Unlike global studies, the socio-technical approach and meso scale facilitate the analysis of cyberspace in international relations. This is an area of both collaboration and conflict for which specific modes of regulation have appeared.
Keywords: Computer Security & Cryptography; Communication System Security; Information Technologies; Electronic books